MD2 in UiTM Perak Branch / Ameri Shariff - Shariff, Ameri (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On March 15, 2019, the first phase of the MD2 pineapple proj-ect had started with the plantation of 200 MD2 pineapple seedlings that were supplied by the State of Perak MPIB to UiTM Perak Branch, Seri Iskandar Campus. The seedlings were planted by the students from various faculties who had registered as the members of MASMED UiTM Perak Branch, particularly MyA-grosis Club (Agro Ladang).